Multilayer radiation protection material, preparation method thereof and protection product
By constructing a multi-layer composite material with a 'mortise and tenon interlocking' structure, the problem of interlayer misalignment is solved, the structural stability and radiation scattering attenuation capability of the material are enhanced, and a highly efficient radiation protection effect is achieved.
Patent Information
- Application Number
- CN202510575534.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-09-23
AI Technical Summary
Existing multilayer composite materials are prone to interlayer dislocation under external loads, resulting in structural instability and reduced scattering attenuation performance.
Wrinkled microspheres with multiple reflective interfaces were prepared by a high-temperature spraying method, and a composite core layer with a raised structure was constructed by a vacuum-assisted filtration method. Finally, a multi-layer composite material with a 'mortise and tenon interlocking' structure was formed by a layer-by-layer assembly method to enhance the interlayer bonding strength and construct a multi-interface alternating structure to improve the scattering attenuation capability.
It significantly enhances the structural stability and ray scattering attenuation efficiency of multilayer composite materials, effectively resists external loads, reduces the probability of interlayer dislocation, and improves ray scattering attenuation efficiency.
Smart Images

Figure BDA0005388436050000131 
Figure BDA0005388436050000141 
Figure HDA0005388436070000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of protective materials, and in particular to a multi-layer radiation protective material, a preparation method thereof, and a protective product. Background Art
[0002] According to the basic principle of the interaction between rays and matter, the attenuation of incident rays is mainly achieved through two mechanisms: absorption and scattering. Therefore, in the existing technology, when designing the radiation shielding performance of materials, the scattering attenuation ability of composite materials to rays can be effectively improved by introducing a multi-interface alternating structure on the basis of strengthening absorption attenuation. Multilayer composite materials show unique advantages in improving the ability to attenuate rays by virtue of the alternating effect between layers. However, in actual application scenarios, such materials face many challenges, such as: the continuous action of external loads, coupled with weak interlayer forces, which makes multilayer composite materials very prone to interlayer dislocation, which not only destroys the original microstructure of the material, but also seriously weakens its scattering attenuation performance to rays.
[0003] In view of this, constructing interlayer connections with special structures and enhancing the interlayer bonding strength of composite materials are of great significance to maintaining the structural stability of the material and improving the radiation shielding performance. Summary of the Invention
[0004] The purpose of the present invention is to provide a multi-layer radiation protection material, a preparation method thereof and a protective product. By constructing a multi-layer composite material with a "mortise and tenon interlocking" structure, the interlayer bonding force between the multi-layer composite materials is greatly enhanced, thereby improving the stability of the material; at the same time, the multi-interface alternating structure further enhances the composite material's ability to attenuate the scattering of incident rays.
[0005] The embodiments of the present invention are achieved through the following technical solutions:
[0006] A method for preparing a multilayer radiation protection material comprises the following steps:
[0007] Step 1: Prepare wrinkled microspheres with multiple reflection interfaces by high-temperature spraying method, specifically:
[0008] First, the functional powder is dispersed in water and stirred thoroughly to prepare a suspension with a concentration of 0.01-0.2g / mL;
[0009] The suspension is then sprayed into an evaporating solvent. Because the evaporating solvent is at a high temperature, the water in the atomized droplets quickly vaporizes. As the water continues to be lost, the functional powder gradually shrinks. After the spraying is completed, a centrifugal operation is performed to achieve initial solid-liquid separation, and the resulting solid is then washed multiple times to remove residual impurities.
[0010] Finally, after drying, wrinkled microspheres with multiple reflection interfaces are obtained;
[0011] Step 2: preparing a composite material core layer having a protruding structure by vacuum-assisted filtration, specifically:
[0012] First, the wrinkled microspheres and the polymer binder are dispersed in an organic solvent and stirred thoroughly to form a uniform mixed solution;
[0013] Subsequently, the mixed liquid is filtered and film-formed in a vacuum environment using a filtration device. Specifically, rough sandpaper is placed below the organic filter membrane in the filtration device as a template. During the filtration process, the wrinkled microspheres and the polymer binder are subjected to negative pressure, tightly adhering to and replicating the rough surface of the sandpaper while gradually solidifying into a film. Due to the presence of raised particles on the surface of the coarse sandpaper, the film is finally formed and solidified, and then dried to obtain a composite material core layer with a raised structure.
[0014] Step 3: Prepare a multilayer composite material with a "mortise and tenon interlocking" structure by layer-by-layer assembly method, specifically:
[0015] First, the polymer is dissolved in an organic solvent, stirred and heated to cause the solvent to evaporate, and an appropriate amount of cross-linking agent is added and stirred evenly to obtain a prepolymer;
[0016] Then, the core layer prepared in step 2 is fixed in a packaging device, and prepolymer is added to both ends of the packaging device to encapsulate both sides of the core layer, and then transferred to a vacuum oven for vacuum defoaming and cured for a period of time, finally obtaining a multilayer composite material with a "mortise and tenon interlocking" structure, that is, obtaining the multilayer radiation protection material;
[0017] Since the core layer surface has a raised structure, during the encapsulation and curing process of the prepolymer, the prepolymer can fully cover the raised structure on the core layer surface due to its good fluidity; as the curing proceeds, the prepolymer gradually forms depressions that fit together with these raised structures. This structure of raised and depressed parts cooperates with each other, just like the traditional mortise and tenon structure, and ultimately constructs a stable structure similar to the "mortise and tenon interlocking", which effectively enhances the interlayer bonding strength of the multi-layer composite material.
[0018] Furthermore, in step 1, the microscopic morphology of the functional powder is a two-dimensional lamellar structure or a one-dimensional nanofiber structure, including but not limited to: Ta4C3T X A mixture of any one or more of MXene nanosheets, boron nitride nanosheets, boron carbide nanosheets, bismuth tungstate nanofibers or lead tungstate nanofibers.
[0019] Furthermore, in step 1, the particle size of the functional powder is 10 nm-50 μm.
[0020] Furthermore, in step 1, the spraying speed of the suspension is 0.2-1 mL / min.
[0021] Furthermore, in step 1, the evaporating solvent is liquid paraffin, and the evaporating temperature is 150-180°C.
[0022] Furthermore, in step 2, the polymer binder includes but is not limited to: any one or more mixtures of polyborosiloxane, polydimethylsiloxane, polyurethane, polyethylene, phenolic resin, cellulose or chitosan.
[0023] Furthermore, in step 2, the organic solvent includes but is not limited to: any one or more mixtures of xylene, cyclohexane, toluene, acetone or tetrahydrofuran.
[0024] Furthermore, in step 2, the rough emery cloth includes emery cloths with different mesh sizes and / or different textures; preferably, the mesh size of the rough emery cloth is 30-2000 meshes.
[0025] Furthermore, in step 2, the mass ratio of the wrinkled microspheres to the polymer binder is 1.5-9:1; the liquid-solid ratio of the volume of the organic solvent to the total mass of the wrinkled microspheres and the polymer binder is 3-20:1 mL / g.
[0026] Furthermore, in step three, the high molecular polymer includes but is not limited to: any one or more mixtures of polyborosiloxane, polydimethylsiloxane, hydrogen-terminated phenyl polysiloxane, polyurethane, polyethylene, chloroprene rubber or phenolic resin.
[0027] Furthermore, in step three, the organic solvent includes but is not limited to: any one or more mixtures of xylene, cyclohexane, toluene, acetone or tetrahydrofuran; the cross-linking agent includes but is not limited to: any one of a platinum catalyst, a vulcanizing agent or boric acid, wherein the vulcanizing agent is a mixture of sulfur and zinc oxide in a mass ratio of 1:3-8; the mass of the cross-linking agent is 0.1-0.5% of the mass of the high molecular weight polymer.
[0028] Furthermore, in step three, the stirring and heating temperature is 30-60° C., the curing temperature is 80-120° C., and the curing time is 1-5 hours.
[0029] Further, in step three, the packaging device includes two oppositely arranged packaging boxes, the interior of the packaging boxes is hollowed out, and one end of the packaging boxes is open, and the open ends of the two packaging boxes are arranged opposite to each other; the top surface of the packaging box is also provided with an opening for pouring prepolymer into the interior of the packaging box; when in use, the core layer material is fixed at the opposite ends of the packaging boxes, and then the prepolymer is cast into the packaging boxes through the openings respectively to encapsulate the two sides of the core layer; the packaging boxes are made of polytetrafluoroethylene material, preferably, the packaging boxes have a diameter of 40-50 mm, an overall depth of 10 mm, a hollow depth of 8 mm; the opening has a depth of 5 mm and a diameter of 10 mm.
[0030] Furthermore, in step three, the number of alternating layers of the multilayer composite material (i.e., the number of times the interface alternates) is 2-100 layers, for example, it can be a "prepolymer-core layer-prepolymer" structure, or a "prepolymer-core layer-prepolymer-core layer-prepolymer" structure, etc.
[0031] The present invention also provides a multi-layer radiation protection material prepared by the above preparation method.
[0032] The present invention also provides a protective product comprising the multi-layer radiation protection material.
[0033] Furthermore, the protective products include protective equipment related to head protection, respiratory protection, eye protection, face protection, hearing protection, hand protection, foot protection and body protection, such as protective clothing, protective gloves, protective hats, etc.
[0034] The technical solutions of the embodiments of the present invention have at least the following advantages and beneficial effects:
[0035] The present invention greatly enhances the interlayer bonding strength between multilayer composite materials by constructing a multilayer composite material with a "mortise and tenon interlocking" structure. This unique structural design can effectively resist the influence of external loads, reduce the probability of interlayer dislocation, and ensure the structural stability of the material under complex working conditions; at the same time, by constructing a multi-interface alternating structure, the scattering and attenuation ability of the composite material to incident rays is further improved; through the above-mentioned structural design, the incident rays in the composite material are repeatedly scattered between different interfaces, which significantly improves the scattering and attenuation efficiency of the rays. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0037] Figure 1 A schematic structural diagram of the rough gauze used in various embodiments of the present invention;
[0038] Figure 2 Schematic diagram of the cross-sectional morphology of the thin film obtained in Experimental Example 3;
[0039] Figure 3 Schematic diagram of the cross-sectional morphology of the film obtained in Comparative Example 2;
[0040] Figure 4 Schematic diagram of the cross-sectional morphology of the multilayer composite material obtained in Example 3 and Comparative Example 2;
[0041] Figure 5 Graphs showing mechanical properties of the multilayer composite materials obtained in Example 3 and Comparative Example 2;
[0042] Figure 6 Schematic diagram of mechanical property test results of the multilayer composite materials obtained in Example 3 and Comparative Example 2;
[0043] Figure 7 Schematic diagram of the mass attenuation coefficient of the multilayer composite materials obtained in Example 3 and Comparative Examples 1-3 to 59.6 KeV gamma rays;
[0044] Figure 8 A schematic structural diagram of a packaging device provided in an embodiment of the present invention;
[0045] Icon: 1-Packaging box, 2-Opening, 3-Composite material core layer. DETAILED DESCRIPTION
[0046] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.
[0047] The following is a detailed description of a multi-layer radiation protection material provided by an embodiment of the present invention, its preparation method, and its application.
[0048] Example 1
[0049] This embodiment provides a method for preparing a multilayer radiation protection material, comprising the following steps:
[0050] Step 1: First, 1gTa4C3T XMXene was dispersed in 10 ml of deionized water and stirred to obtain a suspension. The suspension was sprayed into a 150°C liquid paraffin solvent at a rate of 0.5 mL / min through a syringe pump. After cooling to room temperature, the precipitate at the bottom of the liquid paraffin was collected and washed by centrifugation with cyclohexane and deionized water at a rate of 6000 rad / min. Finally, it was freeze-dried in a freeze dryer at -50°C and below 10 Pa to obtain Ta4C3T3 with a wrinkled interface. X MXene wrinkled microspheres;
[0051] Step 2: Take 1g of Ta4C3T obtained in step 1 X MXene wrinkled microspheres and 0.2g of polyborosiloxane were dispersed in 20ml of xylene solvent and stirred at room temperature to evaporate the xylene solvent to obtain a viscous mixture. Simultaneously, a filtration device was assembled from top to bottom in the order of a filtration funnel, an organic filter membrane, rough emery cloth, and a filter sand core, where the mesh size of the rough emery cloth was 36. The mixture was vacuum-filtered to form a rough film.
[0052] Step 3: First, disperse 4g of polyborosiloxane, 2g of hydrogen-terminated phenyl polysiloxane, and 4g of chloroprene rubber in 50ml of xylene solvent, heat and stir at 40°C to obtain a prepolymer; then add 0.01g of platinum catalyst and stir evenly; then fix the film obtained in step 2 in a packaging device, and add 5g of prepolymer to both ends of the packaging device to package the film, then transfer it to a vacuum oven at room temperature for vacuum defoaming, and cure it at 100°C for 2h to finally obtain a multilayer composite material with a "mortise and tenon interlocking" structure; wherein, the packaging device includes two relatively arranged packaging boxes 1, and the packaging box 1 has two inner portions. The top of the packaging box 1 is hollowed out, and one end of the packaging box 1 is open, and the open ends of the two packaging boxes 1 are arranged opposite to each other; the top surface of the packaging box 1 is also provided with an opening 2 for pouring prepolymer into the interior of the packaging box 1; when in use, the composite material core layer 3 (i.e., film) is fixed at the opposite position of the packaging box 1, and then the prepolymer is cast into the packaging box 1 through the opening 2 to encapsulate the two sides of the composite material core layer 3 (i.e., film); the packaging box 1 is made of polytetrafluoroethylene material, preferably, the packaging box 1 has a diameter of 40-50 mm, an overall depth of 10 mm, and a hollow depth of 8 mm; the opening 2 has a depth of 5 mm and a diameter of 10 mm.
[0053] This embodiment also provides a protective suit comprising the above-mentioned composite material.
[0054] Example 2
[0055] A method for preparing a multilayer radiation protection material comprises the following steps:
[0056] Step 1: First, 1g of boron nitride is dispersed in 10ml of deionized water and stirred to obtain a suspension; the suspension is sprayed into a 150°C liquid paraffin solvent at a rate of 0.5ml / min through a syringe pump, and after cooling to room temperature, the precipitate at the bottom of the liquid paraffin is collected, and cyclohexane and deionized water are centrifuged and washed at a rate of 6000rad / min. Finally, the precipitate is freeze-dried in a freeze dryer at -50°C and below 10Pa to obtain boron nitride wrinkled microspheres with wrinkled interfaces;
[0057] Step 2: Disperse 1 g of the boron nitride wrinkled microspheres obtained in step 1 and 0.2 g of polydimethylsiloxane in 20 ml of xylene solvent, stir at room temperature, and evaporate the xylene solvent to obtain a viscous mixture; simultaneously, assemble a filtration device in the order of a filtration funnel, an organic filter membrane, a rough emery cloth, and a filter sand core from top to bottom, wherein the mesh size of the rough emery cloth is 40 mesh; and filter the mixture by vacuum filtration to form a film with a rough surface;
[0058] Step three, first, disperse 2g of natural rubber, 4g of polydimethylsiloxane, and 4g of polyurethane glue in 30ml of xylene solvent, heat and stir at 40°C to obtain a prepolymer; then add 0.05g of vulcanizing agent and stir evenly; then fix the film obtained in step two in the middle of the packaging device, add 5g of prepolymer to both ends for packaging, then transfer it to a vacuum oven at room temperature for vacuum defoaming, and cure it at 80°C for 2h to finally obtain a multilayer composite material with a "mortise and tenon interlocking" structure.
[0059] Example 3
[0060] A method for preparing a multilayer radiation protection material comprises the following steps:
[0061] Step 1: First, 2 g of bismuth tungstate nanofibers are dispersed in 10 ml of deionized water and stirred to form a suspension; the prepared suspension is sprayed into a 150°C liquid paraffin solvent at a rate of 0.5 ml / min through a syringe pump. After cooling to room temperature, the precipitate at the bottom of the liquid paraffin is collected and centrifuged at a rate of 6000 rad / min using cyclohexane and deionized water. Finally, the precipitate is freeze-dried at -50°C and below 10 Pa using a freeze dryer to obtain bismuth tungstate wrinkled microspheres with a wrinkled interface;
[0062] Step 2: 2 g of the bismuth tungstate wrinkled microspheres obtained in step 1 and 0.5 g of polyurethane are dispersed in 10 ml of tetrahydrofuran solvent, stirred at 40° C., and the tetrahydrofuran solvent is rapidly evaporated to obtain a viscous mixture; at the same time, a filtration device is assembled from top to bottom in the order of a filtration funnel, an organic filter membrane, a rough emery cloth, and a filter sand core, wherein the mesh number of the rough emery cloth is 60 mesh; the above mixture is filtered by a vacuum-assisted method to form a film with a rough surface;
[0063] Step three, first, disperse 4g of polyborosiloxane, 2g of polyvinyl alcohol, and 4g of polyurethane in 50ml of tetrahydrofuran solvent, heat and stir at 50°C to obtain a prepolymer; then add 0.05g of boric acid and stir evenly; then fix the rough film obtained in step two in the middle of the packaging device, add 5g of prepolymer to both ends for packaging, and then transfer it to a vacuum oven at room temperature for vacuum defoaming, and cure it at 80°C for 2h to finally obtain a multilayer composite material with a "mortise and tenon interlocking" structure.
[0064] Example 4
[0065] A method for preparing a multilayer radiation protection material comprises the following steps:
[0066] Step 1: First, 2 g of lead tungstate nanofibers are dispersed in 10 ml of deionized water and stirred to form a suspension of corresponding concentration; the prepared suspension is sprayed into a 150°C liquid paraffin solvent at a rate of 0.5 mL / min through a syringe pump. After cooling to room temperature, the precipitate at the bottom of the liquid paraffin is collected and centrifuged at a rate of 6000 rad / min using cyclohexane and deionized water. Finally, the precipitate is freeze-dried at -50°C and below 10 Pa using a freeze dryer to obtain lead tungstate wrinkled microspheres with a wrinkled interface;
[0067] Step 2: Disperse 2 g of the lead tungstate microspheres obtained in step 1 and 0.4 g of polyborosiloxane in 20 ml of xylene solvent, stir at room temperature, and evaporate the xylene solvent to obtain a viscous mixture; at the same time, assemble a filtration device from top to bottom in the order of a filtration funnel, an organic filter membrane, a rough emery cloth, and a filter sand core, wherein the mesh size of the rough emery cloth is 80 mesh; and filter the mixture by vacuum filtration to form a film with a rough surface;
[0068] Step three, first, disperse 4g of polyborosiloxane, 2g of polyurethane, and 4g of chloroprene rubber in 50ml of xylene solvent, heat and stir at 40°C to obtain a prepolymer; then add 0.05g of vulcanizing agent and stir evenly; then fix the film obtained in step two in the middle of the packaging device, add 5g of prepolymer to both ends for packaging, and then transfer it to a vacuum oven at room temperature for vacuum defoaming, and cure it at 80°C for 2h to finally obtain a multilayer composite material with a "mortise and tenon interlocking" structure.
[0069] Example 5
[0070] A method for preparing a multilayer radiation protection material comprises the following steps:
[0071] Step 1: First, 1gTa4C3T X MXene was dispersed in 10 ml of deionized water and stirred to obtain a suspension. The prepared suspension was sprayed into a 150°C liquid paraffin solvent at a rate of 0.5 ml / min through a syringe pump. After cooling to room temperature, the precipitate at the bottom of the liquid paraffin was collected and washed by centrifugation with cyclohexane and deionized water at a rate of 6000 rad / min. Finally, it was freeze-dried in a freeze dryer at -50°C and below 10 Pa to obtain Ta4C3T3 with a wrinkled interface. X MXene microspheres;
[0072] Step 2: Take 1g of Ta4C3T obtained in step 1 X MXene microspheres and 0.2 g of polyborosiloxane were dispersed in 20 ml of xylene solvent and stirred at room temperature to evaporate the xylene solvent to obtain a viscous mixture. Simultaneously, a filtration device was assembled from top to bottom in the order of a filtration funnel, an organic filter membrane, rough emery cloth, and a filter sand core, where the mesh size of the rough emery cloth was 100 mesh. The mixture was vacuum-filtered to form a film with a rough surface.
[0073] Step three, first, disperse 4g of polyborosiloxane, 4g of polyurethane, and 2g of polyvinyl alcohol in tetrahydrofuran solvent, heat and stir at 50°C to obtain a prepolymer; then add 0.05g of boric acid and stir evenly; then fix the film obtained in step two in the middle of the packaging device, add 5g of prepolymer to both ends for packaging, then transfer to a vacuum oven at room temperature for vacuum defoaming, and cure at 80°C for 2h to finally obtain a multilayer composite material with a "mortise and tenon interlocking" structure.
[0074] Example 6
[0075] The difference between this embodiment and embodiment 1 is that the mesh number of the coarse emery cloth is 120 meshes.
[0076] Comparative Example 1
[0077] The difference between this comparative example and Example 1 is that step 1 is not included, that is, the functional powder is not subjected to wrinkle microspheroidization treatment.
[0078] Comparative Example 2
[0079] The difference between this comparative example and Example 1 is that the filtration device in step 2 does not contain a rough sandpaper layer, that is, the core layer film is not designed with a protruding structure.
[0080] Comparative Example 3
[0081] This comparative example adopts a simple blending method to prepare a composite material, comprising the following steps:
[0082] First, 1gTa4C3T X MXene, 2g polyborosiloxane, 1g hydrogen-terminated phenyl polysiloxane, and 2g chloroprene rubber were dispersed in 50ml xylene solvent, heated and stirred at 40°C, and then 0.01g platinum catalyst was added and stirred evenly; then, it was cast in a polytetrafluoroethylene mold, transferred to a vacuum oven for vacuum defoaming, and cured at 100°C for 2h to finally obtain a simply blended composite material.
[0083] Experimental Example 1
[0084] The rough gauze used in each embodiment is as Figure 1 As shown; Figure 1 In the figure, a~f represent rough gauze with mesh sizes of 36, 40, 60, 80, 100, and 120, respectively. As can be seen from the figure, there are raised particles of different sizes on the surface of the emery cloth, and the roughness of the emery cloth gradually decreases with the increase of mesh size. In addition, Figure 1 It can be seen that as the mesh size increases, the height of the protruding particles per unit area decreases, but the number increases, thereby obtaining a core layer film with a rough surface and different protruding structures.
[0085] Experimental Example 2
[0086] The cross-sectional morphology of the thin films obtained in Experimental Example 3 and Comparative Example 2 was characterized using a high-resolution cold field emission scanning microscope (SEM) and an optical microscope (OM). The samples were pre-treated with gold spraying before characterization. Figure 2 、 Figure 3 ;
[0087] in, Figure 2 a~b are SEM images of the thin film obtained in Experimental Example 3. Figure 2 c~d are optical micrographs of the thin films obtained in Experimental Example 3; Figure 3 a~b are SEM images of the film obtained in Comparative Example 2, Figure 3 c~d are optical micrographs of the film obtained in Comparative Example 2;
[0088] Here, we define the side of the composite material core layer, i.e., the obtained film, that contacts the rough emery cloth as the back side of the core layer, and the side that does not contact the rough emery cloth as the front side of the core layer;
[0089] Since there are particles of different sizes on the surface of the rough abrasive cloth, when the core layer replicates the shape of the abrasive cloth surface, holes of different sizes will be left on the back of the core layer, such as Figure 2 a and 2b ( Figure 2 a and Figure 2 b shows the microscopic morphology of the back side of the core layer prepared with 60-mesh rough sandpaper as the template at scales of 1 mm and 200 μm; at the same time, the front side of the core layer well reproduces the raised particles on the surface of the rough sandpaper, such as Figure 2 c and 2d ( Figure 2 c and Figure 2 d shows the microscopic morphology of the front side of the core layer prepared using 60-mesh rough emery cloth as a template at scales of 1 mm and 200 μm, respectively);
[0090] And by Figure 3 The results of SEM and optical microscopy characterization of the front and back surfaces of the core layer of the core layer film obtained in Comparative Example 2 show that since no rough sandpaper layer was used as a template during the filtration process, and only an organic filter membrane was used, the surface of the organic filter membrane was smooth, so the back surface of the core layer ( Figure 3 a and Figure 3 b) and the front of the core layer ( Figure 3 c and Figure 3 d) are relatively smooth, without any holes or raised granular structures.
[0091] Experimental Example 3
[0092] The cross-sectional morphology of the multilayer composite materials obtained in Example 3 and Comparative Example 2 was characterized by using a high-resolution cold field emission scanning microscope (SEM) and an optical microscope (OM). The samples were pre-treated with gold spraying before characterization. Figure 4 ;
[0093] in, Figure 4 a shows the cross-sectional morphology of the multilayer composite material obtained in Comparative Example 2. It can be seen from the figure that the contact interface between the layers is relatively flat; Figure 4 Figure b shows the cross-sectional morphology of the multilayer composite material obtained in Example 3 (using 60-mesh rough sandpaper as a template to prepare the core layer). It can be seen from the figure that there is an obvious "mortise and tenon interlocking" structure at the contact interface between the layers. The existence of this structure is conducive to enhancing the interlayer force and solving the interlayer misalignment problem that exists in the actual application of the multilayer composite material.
[0094] Experimental Example 4
[0095] 1. The tensile strength, tear strength and pull-out strength of the multilayer composite materials prepared in Examples 1-5 and Comparative Examples 1-2 were tested using a universal tensile test machine according to the test standards GB / T 528-2009 and GB / T 3917.2-2009. The test results are shown in Table 1.
[0096] Table 1 - Mechanical properties test results of different composite materials
[0097]
[0098]
[0099] From the results in Table 1, it can be seen that the tensile strength, tear strength, and pull-out strength of the multilayer composite material prepared in the embodiment of the present invention all show outstanding mechanical advantages. At the same time, it can be seen that with the increase of the mesh size of the template, there is a trend of first increasing and then decreasing. This is mainly because the number of raised particles per unit area of the template surface increases but the particle height decreases. At the same time, the interlayer force between the multilayer composite material is determined by the height and number of the raised particles. Therefore, the above-mentioned law is presented.
[0100] 2. In addition, the mechanical properties test of the multilayer composite material of Example 3 and Comparative Example 2 is demonstrated, see Figure 5-6 ,in, Figure 5 a1. Figure 5 b1. Figure 5 c1 shows the schematic diagrams of tensile test, tear test and pull-out test respectively; Figure 5 a2. Figure 5 b2. Figure 5 c2 shows the digital photos of the tensile test, tear test, and pull-out test respectively; Figure 6 a. Figure 6 b. Figure 6 c are the test results of tensile test, tearing test and pull-out test respectively.
[0101] from Figure 6 It can be seen from a that the tensile strength of the multilayer composite material prepared by using 60 mesh sandpaper as template and without using template is not much different. This is because the raw material composition of the two is the same. Figure 6 b and Figure 6 c It can be seen that the tearing strength and tensile strength of the multilayer composite material prepared using 60-mesh rough emery cloth as a template in Example 3 are significantly better than those of the multilayer composite material prepared without using rough emery cloth as a template in Comparative Example 2. This is because the use of rough emery cloth constructs a "mortise and tenon interlocking" structure between the multilayer materials, and the existence of this structure increases the force between the layers.
[0102] Experimental Example 4
[0103] The shielding performance of the composite materials obtained in Example 3 and Comparative Examples 1-3 against 59.6 KeV gamma rays was characterized to explore the effects of the wrinkled microspheres and the multi-layer alternating structure on the material properties. The test results are shown in Tables 2 and Figure 7 The specific test method is as follows: Use high purity germanium gamma spectrometer and multi-channel analyzer to mix Eu -155 / Am -241The shielding capability of the composite material was tested against gamma-ray sources (E ~ 59.5, 86.55, and 105.31 keV), investigating its shielding capability against 59.6 keV gamma rays. For this measurement, the entire exterior of the device consisted of lead. Inside, from top to bottom, the gamma-ray source, composite sample, and germanium detector were placed coaxially. After passing through the shielding material under test, the intensity of the gamma rays received at the detector end was measured.
[0104] Table 2 - Mass attenuation coefficient data of different composite materials for 59.6KeV γ-rays
[0105] Experimental groups Thickness (cm) <![CDATA[Density (g / cm 3 )]]> <![CDATA[μ m (cm 2 / g)]]> Comparative Example 1 0.121 1.3916 0.516±0.036 Comparative Example 2 0.120 1.5322 0.548±0.022 Comparative Example 3 0.135 1.4765 0.502±0.015 Example 3 0.117 1.4895 0.569±0.025
[0106] Table 2 shows the mass attenuation coefficients of 59.6 KeV gamma rays of Comparative Examples 1-3 and Example 3. It can be seen from Table 2 that in Example 3, the presence of the alternating structure of wrinkled microspheres and rough interfaces is conducive to enhancing the material's attenuation ability to rays, which is consistent with the Figure 7 The results shown are consistent, that is, the γ-ray protection ability of the multilayer composite material prepared in Example 3 is better than that of the comparative examples, indicating that under the premise of the same functional powder content, the construction of wrinkled microspheres and the construction of rough interface alternating structures are carried out simultaneously, and the multilayer composite material prepared can enhance the material's attenuation ability to 59.6KeV γ rays.
[0107] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for preparing a multilayer radiation protection material, characterized in that: The following steps are involved: S1. Preparation of wrinkled microspheres with multiple reflective interfaces by high-temperature spraying; S2. A composite core layer with a raised structure was prepared from wrinkled microspheres using a vacuum-assisted filtration method; S3. Assemble the polymer and the composite material core layer using a layer-by-layer assembly method to prepare a multilayer composite material with a "mortise and tenon interlocking" structure, thereby obtaining the multilayer radiation protection material.
2. The method for preparing a multilayer radiation protection material according to claim 1, characterized in that: S1 includes the following steps: S11, dispersing the functional powder in water, stirring thoroughly, and preparing a suspension with a concentration of 0.01-0.2 g / mL; S12, spraying the suspension into an evaporating solvent, then centrifuging and washing the precipitate multiple times; S13, after drying, wrinkled microspheres with multiple reflection interfaces are obtained.
3. The method for preparing a multilayer radiation protection material according to claim 2, characterized in that: In S11, the microscopic morphology of the functional powder is a two-dimensional lamellar structure or a one-dimensional nanofiber structure; the functional powder includes: Ta4C3T X A mixture of any one or more of MXene nanosheets, boron nitride nanosheets, boron carbide nanosheets, bismuth tungstate nanofibers, or lead tungstate nanofibers; In S12, the spraying speed of the suspension is 0.2-1 mL / min; the evaporating solvent is liquid paraffin, and the evaporation temperature is 150-180°C.
4. The method for preparing a multilayer radiation protection material according to claim 1, characterized in that: S2 includes the following steps: S21, dispersing the wrinkled microspheres and the polymer binder in an organic solvent, and stirring thoroughly to form a mixed solution; S22, using a filtration device to filter the mixed liquid under a vacuum environment to form a membrane, thereby obtaining a core layer of a composite material with a protruding structure; wherein, in the filtration device, a rough sandpaper with protruding particles on the surface is placed below the organic filter membrane.
5. The method for preparing a multilayer radiation protection material according to claim 4, characterized in that: In S21, the polymer binder includes: any one or more mixtures of polyborosiloxane, polydimethylsiloxane, polyurethane, polyethylene, phenolic resin, cellulose or chitosan; the organic solvent includes: any one or more mixtures of xylene, cyclohexane, toluene, acetone or tetrahydrofuran; In S22, the mesh size of the rough emery cloth is 30-2000 mesh; In S21, the mass ratio of the wrinkled microspheres to the polymer binder is 1.5-9:1; the liquid-solid ratio of the volume of the organic solvent to the total mass of the wrinkled microspheres and the polymer binder is 3-20:1 mL / g.
6. The method for preparing a multilayer radiation protection material according to claim 1, characterized in that: S3 includes the following steps: S31, dissolving a high molecular weight polymer in an organic solvent, stirring and heating, adding an appropriate amount of a cross-linking agent, and continuing to stir uniformly to obtain a prepolymer; wherein the mass of the cross-linking agent is 0.1-0.5% of the mass of the high molecular weight polymer; S32, fixing the core layer of the composite material in a packaging device, and adding prepolymer to both ends of the packaging device to encapsulate both sides of the core layer, followed by vacuum defoaming and curing for a period of time, to finally obtain a multilayer composite material with a "mortise and tenon interlocking" structure.
7. The method for preparing a multilayer radiation protection material according to claim 6, characterized in that: In S31, the high molecular polymer includes: any one or more mixtures of polyborosiloxane, polydimethylsiloxane, hydrogen-terminated phenyl polysiloxane, polyurethane, polyethylene, chloroprene rubber or phenolic resin; the organic solvent includes: any one or more mixtures of xylene, cyclohexane, toluene, acetone or tetrahydrofuran; the cross-linking agent includes: any one of a platinum catalyst, a vulcanizing agent or boric acid; the vulcanizing agent is a mixture of sulfur and zinc oxide in a mass ratio of 1:3-8; the mass of the cross-linking agent is 0.1-0.5% of the mass of the high molecular polymer.
8. The method for preparing a multilayer radiation protection material according to claim 6, characterized in that: In S32, the packaging device includes two packaging boxes arranged opposite to each other, the interior of the packaging boxes is hollowed out, and one end of the packaging boxes is open, and the openings of the two packaging boxes are arranged opposite to each other; the top surface of the packaging box is also provided with an opening for casting prepolymer into the interior of the packaging box.
9. A multi-layer radiation protection material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A protective product, characterized in that: The protective product comprises a multilayer radiation protection material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Sensitising silver halide emulsion layers
GB400951A